Pengembangan Strategi Peningkatan Pengunjung dan Konsumen Kantin ITB Ahmad Dahlan - Sutia Budi; Mukhaer Pakkanna (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2020)
This study was to explore the perceptions of ITB Ahmad Dahlan students towards Ahmad Dahlan's ITB canteen, as well as to find out the factors that caused students to want to visit Ahmad Dahlan's ITB canteen. Furthermore, after knowing these factors, this research will give priority to strategies that can be done by Ahmad Dahlan's ITB canteen to increase the number of visitors and consumers. The results showed that the students 'perceptions of the products and promotions of Ahmad Dahlan's ITB canteen were good enough and the students' perceptions of prices and places needed to be improved again. Furthermore, the results of the factors that cause students to visit Ahmad Dahlan's ITB canteen are advertising and social media factors, service quality factors, price factors, product factors, sales promotion factors and process / accuracy factors. The results of the strategy to increase the number of visitors and consumers of Ahmad Dahlan's ITB canteen are strategies to improve product quality, increase sales promotion, pricing strategies, strategies to improve service quality, improve advertising and social media and improve process / accuracy.